Water-surfactant-silica nanoparticles molecular interaction using molecular dynamic technique - Abd Latif, Abd Hafiz (2017)
Enhance oil recovery (EOR) using surfactant flooding has challenge in maintaining the foam during the process. Application of nanotechnology and silica have been found can play a role in helping to EOR but its molecular dynamic interface abilities and interactions behavior not widely known. The molecular dynamic is prediction tool for researchers to predict the output process. It is necessary to simulate the interface of water, Alpha Olefin Sulfonate (AOS) surfactant and silica nanoparticle using molecular dynamics simulations and to study the molecular interactions behaviours and understanding the structural and dynamic information from diffusivity and surface tension. The silica nanoparticles were constructed into a ring shape as to study the interaction in terms of two-dimensional. From the molecular dynamic simulation, the mean square displacement (MSD) graph was plotted to find the diffusivity of the AOS into the system. The cohesive energy density (CeD) was obtained from the simulation and used to calculate the surface tension. The molecular dynamics simulation ran in this study has found that the presence of silica nanoparticle did not improve the mobility of the surfactant. This is because the comparison between a system that does not have the presence of silica nanoparticles shows that its diffusivity value was higher and has lower surface tension than a system contain silica nanoparticles.